2018
DOI: 10.1371/journal.pone.0206380
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MAGGIC (Meta-Analysis Global Group in Chronic Heart Failure) heart failure risk score and the effect of adding natriuretic peptide for predicting mortality after discharge in hospitalized patients with heart failure

Abstract: BackgroundIn clinical practice, a risk prediction model is an effective solitary program to predict prognosis in particular patient groups. B-type natriuretic peptide (BNP)and N-terminal pro-b-type natriuretic peptide (NT-proBNP) are widely recognized outcome-predicting factors for patients with heart failure (HF).This study derived external validation of a risk score to predict 1-year mortality after discharge in hospitalized patients with HF using the Meta-analysis Global Group in Chronic Heart Failure (MAGG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 43 publications
2
42
0
3
Order By: Relevance
“…The GWTG-HF and MAGGIC scores are well validated conventional models for risk stratification of AHF patients. [2326] The previous validation studies have reported that the AUC of the GWTG-HF scores for predicting in-hospital mortality of patients with AHF was 0.71–0.76. [24,25] Furthermore, the AUC of the MAGGIC score for predicting 1–3-year mortality of patients with AHF in previous studies was 0.73–0.74, implying moderate accuracy for predicting the mortality of patients with AHF.…”
Section: Discussionmentioning
confidence: 99%
“…The GWTG-HF and MAGGIC scores are well validated conventional models for risk stratification of AHF patients. [2326] The previous validation studies have reported that the AUC of the GWTG-HF scores for predicting in-hospital mortality of patients with AHF was 0.71–0.76. [24,25] Furthermore, the AUC of the MAGGIC score for predicting 1–3-year mortality of patients with AHF in previous studies was 0.73–0.74, implying moderate accuracy for predicting the mortality of patients with AHF.…”
Section: Discussionmentioning
confidence: 99%
“…In ROC analyses, the risk factors LVEF or MAGGIC score added less predictive power to NT‐proBNP than MR‐proADM, although the difference is small for the MAGGIC score (online supplementary Figures S2 and S3 ). Another study on Asian patients reported only a negligible increase in discrimination (AUC) between survival and 1‐year mortality when NT‐proBNP or BNP was used in addition to the MAGGIC score …”
Section: Discussionmentioning
confidence: 99%
“…Another study on Asian patients reported only a negligible increase in discrimination (AUC) between survival and 1-year mortality when NT-proBNP or BNP was used in addition to the MAGGIC score. 31 Nevertheless, none of these biomarkers, despite sound pathophysiological concepts, was shown to be useful in the guidance of . HF therapy.…”
Section: Biomarkersmentioning
confidence: 99%
“…BNP can represent powerful biological effects, such as natriuresis, vasodilation, myocardial apoptosis inhibition, and modulation of immune and inflammatory responses of cardiac injury [ 12 14 ]. Some prior studies suggest that BNP can be used as a biomarker for prognosis in patients with HF, and it also participates in both occurrence and development of T2DM and ischemic cardiomyopathy [ 15 , 16 ]. What's more, in diabetic patients, BNP can be used for screening the absence of left ventricular dysfunction [ 17 ].…”
Section: Introductionmentioning
confidence: 99%